(untitled) (Journal of Industrial and Mechanical Engineering, 2024)
The industries that produce bio-agricultural inoculants are mostly Small and Medium Enterprises. The production of bio-inputs for monocultures (inoculants) produces seasonality in production, harming activity outside the productive season. The inoculants are made up of nodulating nitrogen-fixing bacteria, a product that improves the productivity, development and maturation of seeds when planting plantations. The application of new technologies that allow solving this variable situation in production is a challenge. The fruitful processes of each species of seeds are different and today it is onerous to diversify in the production of each inoculant for each species. In addition, the sterilization processes themselves could be replaced by new concepts, supported by electromagnetic radiation. We consider that the innovations of Industry 4.0 in production activity would provide an answer to the question. The combined use and integration of these technologies would ensure improvements in processes in traditional monocultures (soybeans) and in others, complementing seasonality without large investments, but with the benefit of productive continuity.